Effect of using digital resources on mathematics achievement: Results from PISA 2022 - Dirgha Raj Joshi; Krishna Prasad Sharma Chapai; Parshu Ram Upadhayaya; Krishna Prasad Adhikari; Shashidhar Belbase (Cogent Education)
This study examines the effect of the usage of digital tools by 15-year-old students on their mathematics achievement. The data for the study was retrieved from the publicly available information in the Program for International Student Assessment (PISA) 2022 database. The six study constructs for this study are: time of using digital resources for learning, digital resource use for learning math content, use of digital resources in feedback, use of digital resources at school, use of digital resources out of school, and use of digital resources during leisure time at schools whereas mathematics achievement score is additional main dependent variable. The sample of the study consists of 256,411 participants. The data were analyzed by using structural equation modeling technique. The findings revealed that the time of using digital resources for learning mathematics and using such resources out of school were the strong predictors of mathematics achievement. While analyzing the mediating effects, time of using digital resources has significant mediating roles in the use of digital resources at school, out of school, and leisure time on mathematics achievement. Likewise, the usage of digital resources at school significantly mediates in relationship between the use of digital resources for learning, use during leisure time, and use for feedback on mathematics achievement.